Security Strategies For State-Owned Assets (BMN) on Land and Buildings at the Ministry of Public Works - Yogi Darmawan; Nurkholis Nurkholis; Zaki Baridwan (Green Publisher Indonesia, 2025)
Securing State Property (BMN), especially land and buildings in the infrastructure sector, is an important element in ensuring the optimization of the use of state assets. In the context of increasingly complex and dynamic asset management, the challenges faced include the risk of loss, damage, and misuse of assets that can interfere with the function and value of these assets. Therefore, the development of effective and adaptive security strategies is very important. This strategy must be able to accommodate the rapid development of digital technology and the need for innovative policies to support transparent and accountable asset governance. This research aims to design and examine BMN security strategies, especially in land and building assets in the infrastructure sector, with a focus on the comprehensive integration of digital information systems. The approach used is qualitative, involving in-depth interviews, field observations, and documentation and analyzed using the Interpretative Phenomenological Analysis (IPA) method. The results of the study identified three main pillars of strengthening BMN security, namely: the application of information technology, policy strengthening, and increasing the capacity of human resources (HR). Information technology plays a crucial role in digitizing asset data, geospatial mapping, and managing legal documents electronically. Strengthening policies is needed to adapt regulations to the dynamics of digitalization, simplifying procedures, and strengthening legal supervision. Meanwhile, increasing the capacity of human resources requires mastery of information technology, data security, and data analysis skills.